IN SILICO ANALYSIS AND MOLECULAR INTERACTIONS STUDIES OF SELECTED PHYTOCONSTITUENTS FROM ANDROGRAPHIS PANICULATA AS POTENTIAL INHIBITORS OF MONOAMINE OXIDASE B - Sankari, Siva; Ramaraj, Kannan; Rajaram, Shyam Kumar; Alexander, Ronaldo Anuf (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of the present study is to explore novel drug lead constituents from Andrographis paniculata for the treatment of Parkinson’s disease. Methods: Phytoconstituents from A. paniculata were screened, and their activity against the monoamine oxidase B (MAO-B) protein was analyzed using Molegro Virtual Docker software. The binding energy and interaction of the phytoconstituents with the protein were analyzed. The phytoconstituents were also analyzed for their compliance toward Lipinski’s rule of five. Results: Molecular docking studies were performed using Molegro Docking software. The compound neoandrographolide exhibited more potent inhibitory activity with a MolDock score of âˆ’126.78 Kcal/mol compared to that of the standard drug Zelapar which exhibited a MolDock score of âˆ’49.95 Kcal/mol. The docked pose of the compound neoandrographolide fits exactly at the active site with a maximum number of H-bond interactions. Conclusion: The present study suggests that neoandrographolide could be used as a potent inhibitor of MAO-B protein. However, it has to be validated using in-vivo and in-vitro studies to suggest the potency of neoandrographolide to inhibit the target protein, which could make neoandrographolide as an effective drug lead for the treatment of Alzhemier’s disease. Keywords: Andrographis paniculata, Monoamine oxidase B protein, MolDock, Alzhemier’s disease.